Experimental study on the development of abrasion at offshore concrete structures in ice conditions - Tijsen, J.N.W. (author) (2015)
Concrete structures in marine environments subject to sea ice interaction are at risk of erosion and damage. Industry is interested in characterizing the ice abrasion phenomenon so that abrasion risk can be managed. The experiments conducted in this work have an exploratory character in order to identify the abrasion phenomenon and qualitatively observe the corresponding processes. The tests are a simulation of micro scale ice-structure interaction and involve the translation of concrete samples while subject to lateral impingement of conical ice samples. Loads in both axes are measured so that tangential and normal force relationship can be examined while the ice samples are catastrophically crushed. The paper divides the interaction into abrasive loading regions and loading orders intentionally to facilitate analysis of the abrasion process. The wear of the concrete surface is described using visual observation and surface feature measurements Concrete of varying mixtures has been examined and the effects on the concrete surfaces from repeated static ice-bonding and bondbreakage is analysed. Master Offshore and Dreding Engineering Maritime and Transport Technology Mechanical, Maritime and Materials Engineering